DETERMINAN STRUKTUR MODAL PERBANKAN DI BURSA EFEK INDONESIA - Hayati, Restu; Sari, Ria Nelly (Jurnal Tepak Manajemen Bisnis, 2016)
This paper aims to analyze the relationships between the determinants of bank capitalstructure to itâs leverage. This study focuses on the use of decomposional analysis to its leverageby applying two main theories of capital structure that are the trade off theory and the peckingorder theory. A decomposional analysis divided leverage into four type indicators of latentvariables that each of these variables calculated again based on the book value and the marketvalue. A decompotional analysis aims to measure the sensitivity of the different measurements ofthe definition of leverage.This study was conducted on 31 banking companies listed in IndonesiaStock Exchange from 2007 to 2012 by purposive sampling method. The nalysis tool used isStructural Equation Model (SEM) with LISREL program. SEM analysis is used to observe theeffect of the policy determinants of capital structure to banking decompositional leverage which isa complex variable, and to obtain an overall picture of the overall models.The results showed thatfactors into the determinants of the capital structure of Indonesia banking industries aretangibility, agency cost, size, and growth were found to significantly affect the decomposition ofleverage. While profitability is proven not significantly affect the decomposition leverage exceptfor leverage-adjusted debt-to-adjusted capital. This study also shows the change in preferredstock, tax rate, and intangible assets as part of leverage can change the significance and directionof the relationship between the factors become determinant of capital structure and leveragelevels.